Identification of Glycoxidative Lesion in Isolated Low-Density Lipoproteins from Diabetes Mellitus Subjects - Amjad R. Alyahyawi; Mohd Yasir Khan; Sultan Alouffi; Farah Maarfi; Rihab Akasha; Saif Khan; Zeeshan Rafi; Talal Alharazi; Uzma Shahab; Saheem Ahmad (Life, 2023)
Methylglyoxal (MG) is a precursor for advanced glycation end-products (AGEs), which have a significant role in diabetes. The present study is designed to probe the immunological response of native and glycated low-density lipoprotein (LDL) in experimental animals. The second part of this study is to probe glycoxidative lesion detection in low-density lipoproteins (LDL) in diabetes subjects with varying disease duration. The neo-epitopes attributed to glycation-induced glycoxidative lesion of LDL in DM patients’ plasma were, analyzed by binding of native and MG-modified LDL immunized animal sera antibodies using an immunochemical assay. The plasma purified human LDL glycation with MG, which instigated modification in LDL. Further, the NewZealand-White rabbits were infused with unmodified natural LDL (N-LDL) and MG-glycatedLDL to probe its immunogenicity. The glycoxidative lesion detection in LDL of DM with disease duration (D.D.) of 5–15 years and D.D. > 15 years was found to be significantly higher as compared to normal healthy subjects (NHS) LDL. The findings support the notion that prolonged duration of diabetes can cause structural alteration in LDL protein molecules, rendering them highly immunogenic in nature. The presence of LDL lesions specific to MG-associated glycoxidation would further help in assessing the progression of diabetes mellitus.